Gestão Democrática e Participação Familiar no Âmbito da Educação Infantil - Bianca Cristina Côrrea (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The present work presents reflections concerning democratic administration and family participation in the infantile education that were part of my Dissertation of Master's degree. The main objective of the research was to observe existent practices or potentials of participation of the families in the infantile education. The work incuded as the bibliographical research as field research, this last one accomplished along one year in municipal school of infantile education (EMEI) in the city of São Paulo that assists children from 4 to 6 years. The results of the research indicated that, although there was effort on the part of the professionals of the school in accomplishing a quality work to involve the participation of the families, also counted with institutionalized mechanisms of participation and adopted other actions to promote it, it lacked speakers to discuss its practice heading to the wanted objectives.